Lornoxicam Alone and with Selegiline Improves the Neuroprotective Effect and Cognition in Scopolamine Induced Neurodegeneration and Cognitive Impairment in Rats: Neuroprotective Effect of Lornoxicam and Selegiline - Sainath Reddy K,; Kaleem A.K,; Sharvana Bhava B.S,; Satish P,; Aravind P,; Venkateshwarlu E, (Iranian Journal of Pharmaceutical Sciences, 2013)
Alzheimer is a progressive neurodegenerative disorder in which Oxidative stress plays a major role. The present study was designed to investigate Neuroprotective effect of Lornoxicam, Selegiline and co-administration of both drugs in Scopolamine induced cognitive impairment and neurodegeneration. Scopolamine (1.4mg/kg) was administered intraperitoniallyin male Wistar rats. Rectangular maze performance test was used to assess the memory performance test. Various biochemical parameters such as Catalase, 1, 1-diphenyl-2- picrylhydrazine (DPPH), Thiobarbituric acid reactive substances(TBARS), reduced glutathione(GSH) and acetylcholine esterase (AchE) were also assessed. IntraperitonialScopolamine results marked memory impairment and oxidative damage. Sub-acute treatment with Lornoxicam (1.3mg/kg, p.o) and Selegiline (0.49mg/kg, p.o) and co-administration of these two drugs for 8 days significantly attenuated scopolamine induced oxidative damage and neurodegeneration. Besides, Lornoxicam, Selegiline and co-administration of both significantly reversed Scopolamine administered increase in acetylcholine esterase activity. Present study indicates protective effect of Lornoxicam, Selegiline and co-administration of both drugs against Scopolamine induced cognitive impairment and oxidative damage. The memory enhancing capacity of the drugs was very significant when compared with disease control (P <0.001).